Projects of Consequence: Interdisciplinary WIL Projects Designed to Meet the Needs of Partners and Students - Piggott, Leanne; Winchester-Seeto, Theresa (Journal of University Teaching and Learning Practice, 2020)
The focus of this paper is the design and development of an innovative project-based work-integrated learning (WIL) course that enables undergraduate students from all faculties to work in interdisciplinary teams with partner organisations from the public, private, and community sectors. Projects are co-designed with partners interested in students from multiple disciplines bringing insights to problems that might not otherwise be resourced by their organisation. These ‘projects of consequence’ are unstructured, ambiguous and complex, requiring student teams to synthesise their different disciplinary knowledge. Student learning is supported by course curriculum design that includes proven pedagogical practices such as: ongoing feedback from partners; students working in autonomous small teams; academic supervision of teamwork; learning support before and during project work; debriefing; providing a safe, supportive space to experiment with new ideas, embracing the prospect of failure and to develop resilience; all underpinned by reflection so as to process, understand and integrate students’ experiences. The versatility of the course design was demonstrated by the rapid change from face-to-face delivery to an entirely online learning environment in response to the COVID-19 pandemic. The challenges and adaptations include changes to the way student teams worked, the additional support needed by students, and adjustment in the mode of interactions with partners.